LSB Embedding in Spatial Domain - A Review of Improved Techniques (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Steganography - the art and technique of hiding information in images, audio, video or text and other cover media has evolved and developed with time. Numerous improvements have been achieved with respect to security, robustness and capacity. This paper presents a review of different LSB embedding techniques in Spatial Domain for image steganography. A variety of techniques which have evolved over time and have improved the basic LSB technique have been discussed. These techniques have also been compared on the basis of different parameters.